The Role of Racial Identity and Implicit Racial Bias in Self-Reported Racial Discrimination: Implications for Depression Among African American Men. (November 2017) - Chae, David H.; Powell, Wizdom A.; Nuru-Jeter, Amani M.; Smith-Bynum, Mia A.; Seaton, Eleanor K.; Forman, Tyrone A.; Turpin, Rodman; Sellers, Robert
Racial discrimination is conceptualized as a psychosocial stressor that has negative implications for mental health. However, factors related to racial identity may influence whether negative experiences are interpreted as instances of racial discrimination and subsequently reported as such in survey instruments, particularly given the ambiguous nature of contemporary racism. Along these lines, dimensions of racial identity may moderate associations between racial discrimination and mental health outcomes. This study examined relationships between racial discrimination, racial identity, implicit racial bias, and depressive symptoms among African American men between 30 and 50 years of age ( n = 95). Higher racial centrality was associated with greater reports of racial discrimination, while greater implicit anti-Black bias was associated with lower reports of racial discrimination. In models predicting elevated depressive symptoms, holding greater implicit anti-Black bias in tandem with reporting lower racial discrimination was associated with the highest risk. Results suggest that unconscious as well as conscious processes related to racial identity are important to consider in measuring racial discrimination, and should be integrated in studies of racial discrimination and mental health.